2012
DOI: 10.1007/s00484-012-0613-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of “Cold Spell” indices to quantify excess chronic obstructive pulmonary disease (COPD) morbidity during winter (November to March 2000–2007): case study in Porto

Abstract: The aim of this study was to examine the relationship between the occurrence of cold episodes and excess hospital admissions for chronic obstructive pulmonary disease (COPD) in Porto, Portugal, in order to further understand the effects of cold weather on health in milder climates. Excess COPD winter morbidity was calculated from admissions for November to March (2000-2007) in the Greater Porto Metropolitan Area (GPMA). Cold spells were identified using several indices (Díaz, World Meteorological Organization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 54 publications
2
23
0
14
Order By: Relevance
“…Similar to the modification effects of intensity, duration and timing of heat waves541, the current study found that the characteristics of cold spells might have also played an important role in the mortality risk of cold spells in China. Similar findings have also been reported in previous studies183742. In our study, we found that there was a significant increase in non-accidental mortality for longer, stronger and earlier cold spells.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the modification effects of intensity, duration and timing of heat waves541, the current study found that the characteristics of cold spells might have also played an important role in the mortality risk of cold spells in China. Similar findings have also been reported in previous studies183742. In our study, we found that there was a significant increase in non-accidental mortality for longer, stronger and earlier cold spells.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is neither a uniform and agreed definition of a cold spell34 nor a precise definition of the period for which such events should be studied. Our criterion for identifying a cold period was to combine time and temperature thresholds, which is similar to that of other studies 35 36. We found that there was a 15.99% increase in pneumonia hospital admissions in the cold period.…”
Section: Discussionmentioning
confidence: 73%
“…Kumi e Ayres (2007) expõem que a diminuição de 1ºC nas temperaturas abaixo de 5ºC está associada ao aumento de 10% das consultas médicas por DPOC. Além destes, Monteiro et al (2013a), para os invernos entre 2000 e 2007 no Porto, apontam que os casos de extremos de frio ≤5ºC podem ser mais significativos no aumento da morbidade por DPOC.…”
Section: Análises Estatísticas Entre As Odc As Odf E a Dpocunclassified
“…No que diz respeito às ondas de calor (OdC) e às ondas de frio (OdF), os exemplos só no novo milênio são vários (e.g. Huynen et al, 2001;Anderson, Bell, 2009;D'Ippoliti et al, 2010;Barnett et al, 2012;Monteiro et al, 2013a;Silveira et al, 2018). .…”
unclassified